2016
DOI: 10.7287/peerj.preprints.2331v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA-seq reveals more consistent reference genes for gene expression studies in human non-melanoma skin cancers

Abstract: Identification of appropriate reference genes (RGs) is critical to accurate data interpretation in quantitative real-time PCR (qPCR) experiments. In this study, we have utilised next generation RNA-sequencing (RNA-seq) to analyse the transcriptome of a panel of non-melanoma skin cancer lesions, identifying genes, which are consistently expressed across all samples. Genes encoding ribosomal proteins were amongst the most stable in this dataset. Validation of this RNA-seq data was examined using qPCR to confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Hence, by using a large collection of RNA-Seq datasets as the one presented here, one can not only evaluate commonly used reference genes, but also propose new ones. By employing a previously developed method (Hoang et al, 2017), we inferred 452 HK genes (Table S6). We evaluated expression levels of each gene in tissues with at least 10 samples and found that HK genes had very low expression variation ( Figure 4A).…”
Section: Housekeeping Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, by using a large collection of RNA-Seq datasets as the one presented here, one can not only evaluate commonly used reference genes, but also propose new ones. By employing a previously developed method (Hoang et al, 2017), we inferred 452 HK genes (Table S6). We evaluated expression levels of each gene in tissues with at least 10 samples and found that HK genes had very low expression variation ( Figure 4A).…”
Section: Housekeeping Genesmentioning
confidence: 99%
“…We selected 11 tissues with at least 10 samples, which resulted in 1225 samples. The variability in gene expression was evaluated as previously described (Hoang et al, 2017). The following criteria were applied to identify HK genes:…”
Section: Identification Of Hk Genesmentioning
confidence: 99%
“…All mRNA primer sequences and amplification efficiencies can be found in Supplementary Table 1. All gene expression was normalized to Rpl7a due to its widespread use and proven stability [29,30].…”
Section: Gene Expressionmentioning
confidence: 99%
“…However, according to the results of a study reported by Bai, rpoD was a stable internal reference gene in Pseudomonas brassicacearum GS20 [41]. Therefore, it could be inferred that the internal reference genes exhibited specificity [42].…”
Section: Discussionmentioning
confidence: 99%